Behavioral Integrity and its Reflection in Humble Leadership: An Exploratory Study of the Views of a Sample of Professors of Imam AL - Kadhim College «Sections of Babylon» - Al-Obeidi, Essam (The Arab Journal of Administration, 2019)
The current research aims to identify the nature of the relationship between Behavioral Integrity and Humble Leadership by seeking the views of a number of teaching staff working in Imam Kadhim College - sections of Babylon, and to this end the researcher distributed 55 questionnaires on the research sample, retrieved 53 questionnaire them, and the response rate 96%. After statistical analysis found the results to the existence of a positive relationship between the Behavioral Integrity and Humble Leadership. As well as having a positive and significant effect of Behavioral Integrity on Humble Leadership. On this basis it has been developing a number of recommendations including the need to stimulate the professors of Imam Kadhim College - sections of Babylon on the possession of skills and capabilities and capacities of Behavioral to achieve the objectives of the College. With the need to encourage them to adopt a regulatory approach rhetoric that leads to lay the foundations to enable them to do the right things at the right times.